Visualizing affective democracy: Learning community in China and Taiwan through images of foreigners - CALLAHAN, William A. (Institutional Knowledge at Singapore Management University, 2023)
In the past few years, cross-strait relations have been in the news again, especially in terms of China’s hard power reunification strategy and its sharp power influence operations. Indeed, much ink has been spilled about what lessons Russia’s invasion of Ukraine has for a possible Chinese invasion of Taiwan. Taiwan’s presidential election in January 2024 has also led to increased analysis on Beijing’s use disinformation, misinformation, and other influence operations to favor candidates more friendly to the PRC. Indeed, Chinese military’s daily testing of Taiwan’s air and sea defense is both a hard power and a sharp power strategy because it wears down both material capabilities and psychological endurance. This article contextualizes and analyzes recent China-Taiwan tensions by examining the soft power of how Beijing and Taipei construct political community through compulsory education. While much research examines history and geography textbooks to show how China and Taiwan have engaged in nation-building—specifically building Chinese or Taiwanese nationalism—over the past decades, this article takes a broader view of identity beyond nationalism to focus on how civic education textbooks work to build community in local, national, and global space. Importantly, it compares Chinese and Taiwanese textbooks to see how they imagine their nations and the world in different ways.